2009
DOI: 10.1002/aoc.1604
|View full text |Cite
|
Sign up to set email alerts
|

An alternative CuCl–piperidine‐catalyzed oxidative homocoupling of terminal alkynes affording 1,3‐diynes in air

Abstract: CuCl with the use of a catalytic amount of piperidine as additive shows high catalytic activity for the oxidative homocoupling reactions of terminal alkynes in toluene at 60• C in air to afford 1,3-diynes in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…119 High yields were obtained for a variety of substrates, although higher temperatures were necessary in comparison to classical conditions. In an effort to identify a “greener” modification of the Hay coupling, Chen and coworkers reported solvent-free conditions, using just 3 mol% CuCl and 3 mol% pyridine in air.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…119 High yields were obtained for a variety of substrates, although higher temperatures were necessary in comparison to classical conditions. In an effort to identify a “greener” modification of the Hay coupling, Chen and coworkers reported solvent-free conditions, using just 3 mol% CuCl and 3 mol% pyridine in air.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…[9][10][11][12] In most experiments, a ligand excess or an external base is added because it has been demonstrated that the reaction is faster under basic conditions. Different bases ranging from ammonium hydroxide employed by Glaser to organic amines [11][12][13] (e.g. piperidine, NEt 3 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the originally employed palladium/copper and other bicatalyst systems for oxidative couplings of terminal alkynes, numerous efforts have been made to explore easy, low‐cost and efficient new procedures to run these reactions. The employment of a single alternative transition metal catalyst such as palladium, copper, nickel and cobalt in the reactions has been found to be an improved protocol in terms of atom economics. In addition, discovering new oxidants constitutes another frontier of the modern Glaser reaction.…”
Section: Introductionmentioning
confidence: 99%